Where to Cross Over? Defining Crossover Sites in Plants - Dluzewska, Julia; Szymanska, Maja; Ziolkowski, Piotr A. (Frontiers in Genetics, 2018)
It is believed that recombination in meiosis serves to reshuffle genetic material from both parents to increase genetic variation in the progeny. At the same time, the number of crossovers is usually kept at a very low level. As a consequence, many organisms need to make the best possible use from the one or two crossovers that occur per chromosome in meiosis. From this perspective, the decision of where to allocate rare crossover events becomes an important issue, especially in self-pollinating plant species, which experience limited variation due to inbreeding. However, the freedom in crossover allocation is significantly limited by other, genetic and non-genetic factors, including chromatin structure. Here we summarize recent progress in our understanding of those processes with a special emphasis on plant genomes. First, we focus on factors which influence the distribution of recombination initiation sites and discuss their effects at both, the single hotspot level and at the chromosome scale. We also briefly explain the aspects of hotspot evolution and their regulation. Next, we analyze how recombination initiation sites translate into the development of crossovers and their location. Moreover, we provide an overview of the sequence polymorphism impact on crossover formation and chromosomal distribution.